Controversies on the Economic Effects of Fixed - Term Employment - Evidence from the OECD Countries - Kwiatkowski, Eugeniusz (Olsztyn Economic Journal, 2016)
This paper focuses on fixed-term employment in the OECD countries, its trends and conditions, as well as controversies regarding its significance for flexibility of employment and labour market segmentation. Statistical data show that fixed-term employment significantly increased its share in total employment in many OECD countries in the last quarter century. The reasons of this trend can be sought in the lower labour cost of this type of employment, and the ease with which this group of employees can be dismissed, which was in part a result of the relaxed legal protection of fixed-term employment in the nineties. Analyses indicate that the increase in the share of fixed-term employment affect employment elasticity nonlinearly according to the shape of the letter U. The analyses support the hypothesis about the segmentation of the labour market as a result of the development of fixed-term employment.